2015
DOI: 10.1007/s00277-015-2308-0
|View full text |Cite
|
Sign up to set email alerts
|

Porcine antilymphocyte globulin (p-ALG) plus cyclosporine A (CsA) treatment in acquired severe aplastic anemia: a retrospective multicenter analysis

Abstract: Severe aplastic anemia (SAA) is a life-threatening bone marrow failure syndrome characterized by pancytopenia and hypocellular bone marrow. Antithymocyte globulin (ATG) is the drug of choice for immunosuppressive therapy (IST) in patients with SAA ineligible for allogeneic stem cell transplantation. This study aimed to evaluate the efficacy and safety profile of porcine antilymphocyte globulin (p-ALG) plus CsA in the treatment of acquired SAA. Clinical information of 69 SAA patients treated with p-ALG plus CsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Some studies [33,36] indicated that P-ATG showed similar efficacy and safety profiles to R-ATG in immunosuppressive therapy of acquired SAA. P-ATG could be a suitable alternative preparation for R-ATG with the advantage of lower medical expense.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [33,36] indicated that P-ATG showed similar efficacy and safety profiles to R-ATG in immunosuppressive therapy of acquired SAA. P-ATG could be a suitable alternative preparation for R-ATG with the advantage of lower medical expense.…”
Section: Discussionmentioning
confidence: 99%
“…It is 40% cheaper than r-ATG and has been widely used as an IST agent for AA in China. 10,11 Despite its extensive use, no studies have compared the efficacy and safety of p-ALG vs r-ATG combined with CSA as a first-line IST for children with AA. In this retrospective study, we analyzed the response rates, adverse events and toxicity, and long-term survival of 189 pediatric patients with AA treated with p-ALG or r-ATG plus CSA.…”
mentioning
confidence: 99%
“…In a prospective study, the cumulative recurrence rate at 3 years follow-up was 28% for horse ATG and 11% for rabbit ATG (no significant difference) (16). We notice that in other reports of porcine ATG, the relapse rates were also very low at 1.4-2.1% (6,17). However, as 73.5% of the patients we analyzed were younger than 40 years old, we think that this may also contribute to the low relapse rate and good response rate.…”
Section: Discussionmentioning
confidence: 70%